52.6k views
4 votes
Answer if you know

don't copy



\green{((2^x + 22^x + 222^x))/((3^x + 33^x + 333^x)) =( 9)/(4)}

2 Answers

4 votes

Answer:-


\bold{\blue{(2^(x)+(22)^(x)+(222)^(x))/(3^(x)+(33)^(x)+(333)^(x))=(9)/(4)}  }


\bold{\pink{(2^(x)+(22)^(x)+(222)^(x))/(3^(x)+(33)^(x)+(333)^(x))=[(4)/(9)]^(-1) }}


\bold{\green{(2^(x)(1+11^(x)+111^(x)))/(3^(x)(1+11^(x)+111^(x)))=(((2)/(3))^{{{2}}})^{{{-1}}}   }}


\bold{\orange{\frac{2^(x)\cancel{(1+11^(x)+111^(x))}}{3^(x)\cancel{(1+11^(x)+111^(x))}}=((2)/(3))^(-2)   }}


\bold{\purple{(2^(x))/(3^(x))=((2)/(3))^(-2)   }}


\bold{\red{((2)/(3))^(x) =((2)/(3))^(-2)   }}


\bold{\green{ x=-2 } }

User Sandy Gifford
by
4.6k points
4 votes

Answer:

Explanation:

simplify upper n lower fraction of LHS:

2^x+22^x+222^x

= 2^x*1 + (2*11)^x + (2*111)^x

= 2^x*1 + 2^x*11^x + 2^x*111^x

= 2^x*(1+11^x+111^x)

3^x+33^x+333^x

= 3^x*1 + (3*11)^x + (3*111)^x

= 3^x*1 + 3^x*11^x + 3^x*111^x

= 3^x*(1+11^x+111^x)

so LHS

= 2^x*(1+11^x+111^x) / (3^x*(1+11^x+111^x))

= 2^x / 3^x

= (2/3)^x

RHS = 9/4

= (3^2/ 2^2)

= (3/2)^2

= (2/3)^(-2)

so x = -2

User Jianwei
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.